PENGARUH JENIS MULSA DAN PUPUK KNO3 TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Andri Rizki Sihombing; Saripah Ulpah; Raisa Baharuddin (DINAMIKA PERTANIAN, 2022)
In the Tomato cultivation in the lowlands, environmental factors such as temperature and humidity are things that need to be considered in order to increase the growth and production of tomatoes. Therefore, it is necessary to modify the environmental conditions with applying mulch, such as plastic mulch or organic mulch. In addition, increased production can be done by fertilizing potassium nitrate (KNO3) which is more practical to use because it has two nutrient contents, namely potassium and nitrogen. The purpose of this study was to determine the effect of the interaction between mulch and potassium nitrate (KNO3) on the growth and production of tomato (Lycopersicum esculentum Mill.). This study used a completely randomized design (CRD) with two factorials. The first factor was the type of mulch which consists of 4 levels of treatment, which are without mulch, black silver plastic mulch, rice straw mulch, reed mulch. The second factor was the concentration of potassium nitrate (KNO3) which consists of 4 levels of treatment, namely 0, 3, 6, 9 g / l. Each treatment was repeated 3 times, in order to obtain 48 experimental units. The results showed that the interaction effect of the type of mulch and potassium nitrate (KNO3) was significant on the parameters of plant height, harvest age, number of fruits per plant, fruit weight per plant, fruit weight per fruit, and number of residual fruits. The best treatment combination was the use of rice straw mulch and a concentration of 9 g/l KNO3 fertilizer.